Edukasi Literasi Keuangan Digital dan Gaya Hidup Konsumtif pada IMM Rosyad Sholeh: Digital Financial Literacy Education and Consumer Lifestyle at IMM Rosyad Sholeh - Nindiasari, Avininda Dewi; Warastri, Annisa; Ningrum, Iin Setya; Mulidinisa, Siti Anggraeni; Wulandari, Fatma Dwi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This community development activity aims to provide education on digital financial literacy and consumer lifestyles to IMM Rosyad Sholeh, Faculty of Economics, Social Sciences and Humanities, Aisyiyah University, Yogyakarta, Indonesia. This activity is a collaborative community development activity involving accounting and psychology knowledge. This community development activity was attended by IMM colleague Rosyad Sholeh. Implementation of community development activities will be carried out directly on Sunday, June 30 2024 at Universitas Aisyiyah Yogyakarta, Indonesia. The results of this activity explain understanding digital financial literacy through financial management through the Jago and Bibit applications. Not only that, there is an understanding of consumer lifestyles to be able to understand and control expenses that are not necessities. The usefulness of this educational activity can be seen from the increase in scores from the pre-test of 81.74% and post-test of 88.26%, a survey of participant satisfaction levels with 80% very satisfied and 20% satisfied with the implementation of this activity. It is hoped that this activity can be continued both from the participants' side to be able to provide financial literacy to the surrounding environment and the community development team can develop educational materials on financial literacy and consumer lifestyles using video or comic media.